Islamic Worldview, Economics and Islamic Economics - Tahir, Sayyid (Intellectual Discourse, 2026)
This article explores the rationale for Islamic economics and some possibilities for developing it based on the Islamic worldview. For reasons recorded in the paper, the Qur’an is chosen as the basis for inquiry. The quest for an Islamic worldview is guided by four factors: Allah SWT’s relationship to all the creation, the nature of worldly life for humans, the position of humankind vis-à-vis all other creation and the position of an individual versus other humans. The Islamic worldview is articulated in relation to the following key points: (i) Allah is the original, absolute and ultimate owner of everything in the heavens and the earth, (ii) the universe has internal consistency, (iii) a cause-and-effect mechanism is always at work, and (iv) life is a test for humans with Divine permission for personal ownership (the right to title as well as use) and freedom of choice (including obeying or disobeying Allah). Recognition of the Will of Allah as the primary guiding principle for the conduct of life, provides the foundational rationale for Islamic economics and shapes its intellectual discourse. Some conclusions are also drawn for developing Islamic economics as an academic discipline.